2003
DOI: 10.1053/jhep.2003.50451
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein regulates transactivation activity and protein stability of the cancer-amplified transcription coactivator ASC-2

Abstract: H epatitis B virus (HBV) mainly infects liver tissue and is associated with hepatitis and hepatocellular carcinoma. 1 Several findings suggest that HBV X protein (HBx) could be a causative factor in progression of these diseases. 2 HBx protein is known to regulate transcription of a variety of cellular and viral genes, although it does not bind to double-stranded DNA. The observation that genes stimulated by HBx lack any obvious consensus sequences suggests that HBx stimulates transcription by interacting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…It's interesting to note that HBx can exert its function on the ubiquitin protein degradation system in either a positive or negative manner . Many studies have demonstrated that HBx can interact with and hijack ubiquitin ligase to target proteins for degradation; yet, other studies have found that HBx can also inhibit ubiquitin ligase and thus stabilize target proteins, such as Pituitary Tumor‐Transforming Gene 1, protein arginine N‐methyltransferase 1, and Amplified in Breast Cancer 1, as we found for WDR5 in this study. Although the HBx‐E3 ubiquitin ligase interaction may inhibit ubiquitination of target proteins, thereby stabilizing them, the underlying mechanism still needs to be elucidated.…”
Section: Discussionsupporting
confidence: 60%
“…It's interesting to note that HBx can exert its function on the ubiquitin protein degradation system in either a positive or negative manner . Many studies have demonstrated that HBx can interact with and hijack ubiquitin ligase to target proteins for degradation; yet, other studies have found that HBx can also inhibit ubiquitin ligase and thus stabilize target proteins, such as Pituitary Tumor‐Transforming Gene 1, protein arginine N‐methyltransferase 1, and Amplified in Breast Cancer 1, as we found for WDR5 in this study. Although the HBx‐E3 ubiquitin ligase interaction may inhibit ubiquitination of target proteins, thereby stabilizing them, the underlying mechanism still needs to be elucidated.…”
Section: Discussionsupporting
confidence: 60%
“…For example, Jab1 (Jun activation domain-binding protein 1) interacts with HIF-1␣ (hypoxia-inducible factor 1␣) and enhances HIF-1␣ stability, resulting in an increase in the HIF-1␣ protein level (1). In a similar way, hepatitis B virus X protein and p300 increase the half-life of activating signal cointegrator 2 and sterol regulatory element binding proteins (SREBPs), respectively (19,31). Thus, the increase of protein stability by protein-protein interaction is likely another action mode of transcription factor/coactivator to enhance gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…SRG3 upregulates the SRC-1 protein level. Interactions between two coactivators or between a nuclear receptor and its coactivator have been reported to increase the stability of one of the participant proteins, resulting in an upregulation of the protein level (1,19,31). Because SRG3 cooperated with SRC-1 in the enhancement of AR transactivation, most likely via physical association, we examined the effect of SRG3 on the SRC-1 protein level in HeLa cells cotransfected with AR, SRC-1, and the control ␤-galactosidase expression plasmids with or without the SRG3 expression vector.…”
Section: Androgen Regulates the Expression Of Srg3 In Rat Prostatementioning
confidence: 99%
“…m67-Luc construct (high-affinity binding site for Stats followed by the luciferase gene) was kindly provided from Dr. Jacqueline Bromberg [30]. pcDNA3/HA/HBx derived from HBV adr subtype, pGL3B/PEPCK promoter, and pCMX1/C/EBPα were previously described [6], [31], [32].…”
Section: Methodsmentioning
confidence: 99%